SEDIMENT ACCUMULATION RATES IN COASTAL AREA OF MURIA PENINSULA, CENTRAL JAVA, ELUCIDATED FROM ENVIRONMENTAL ISOTOPE 210Pb - Ali Arman Lubis; Heni Susiati (Pusat Kajian Sistem Energi Nuklir, Badan Tenaga Nuklir Nasional, 2011)
ABSTRACTSEDIMENT ACCUMULATION RATES IN COASTAL AREA OF MURIA PENINSULA, CENTRAL JAVA, ELUCIDATED FROM ENVIRONMENTAL ISOTOPE 210Pb. Sediment accumulation rates was investigated based on the profiles and inventories of 210Pb and Constant Rate of Supply (CRS) model in sediment cores collected from the coastal area of Muria Peninsula. Sediment cores were collected using gravity corer. The derived sediment accumulation rates vary along the coastline and along the cores and appear to be higher in the eastern part than western part of the site; i.e, between 0.5 to 3.4 kg/m2.y on the eastern part, 0.3 to 3.1 kg/m2.y in the central and 0.5 to 2 kg/m2.y on the western part. Highly deposited sediment may relate to the change in the up-land as well as in the coastal area itself.Keywords: sediment rate, 210Pb, CRS model ABSTRAKLAJU AKUMULASI SEDIMEN DI AREA PESISIR SEMENANJUNG MURIA, JAWA TENGAH, DENGAN ELUSIDASI LINGKUNGAN ISOTOP 210Pb. Telah dilakukan investigasi laju akumulasi sedimen berdasarkan profil dan inventori dari 210Pb dan model Constant Rate of Supply (CRS) pada sedimen core yang diperoleh dari daerah pesisir Semenanjung Muria. Sedimen diambil menggunakan alat gavity core. Laju akumulasi sedimen yang diperoleh bervariasi sepanjang pesisir dan sepanjang core dan untuk laju tersebut lebih tinggi di sebelah timur dibandingkan dengan daerah sebelah barat, yaitu antara 0,5 hingga 3,4 kg/m2.tahun di sebelah timur, 0,3 hingga 3,1 kg/m2.tahun in bagian tengah dan 0,5 hingga 2 kg/m2.tahun di sebelah barat. Laju deposit sedimen yang tinggi kemungkinan disebabkan oleh perubahan di daerah daratan dan daerah pesisir tersebut.Kata kunci: laju sedimen, 210Pb, model CRS